“She did make defect perfection”—The Perfection of the Female Monster: Shakespeare’s Cleopatra and the Querelle des Femmes - Stella, Massimo (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (Iter Press, 2023)
“She did make defect perfection” (Antony and Cleopatra 2.2.242): by this formula, Enobarbus sums up the essence of Cleopatra’s inimitable charm. Shakespeare’s Cleopatra is a study of women and women: in other words, Shakespeare’s Cleopatra is less fiction than an investigation of the other sex. “Was will das Weib?” asked Freud (if we are to believe Marie Bonaparte’s testimony), thus admitting that the great question psychoanalysis has been unable to answer is the enigma of feminine desire. Shakespeare’s Cleopatra represents this enigma, which takes the form of a perfection resulting from a series of paradoxes: beauty and maturity, cunning and folly, fidelity and betrayal, jealousy and indifference, majesty and debauchery, expense and economy, audacity and fragility, truth and lies. Cleopatra’s perfection is the sum of all possible paradoxes. What is the point of this dizzying interplay of paradoxes? What is the resulting perfection?